Hormonal Regulation for de novo Organogenesis in in vtro Derived Leaf and Internode of dAegle marmelos L. - Mishra, Yogeshwar; Bhadrawale, Deepti; Mishra, Jay Prakash; Singh, Vikram; Dhurve; Shirin, Fatima (Indian Forester, 2021)
Adventitious shoot formation from internode explants of Aegle marmelos was achieved. Leaf and internode explants were procured from shoots obtained from in vitro germinating seedlings.Â  Callogenesis was induced from leaf and internode explants on Murashige and Skoog (MS) semisolid medium variously supplemented with 6-Benzyladenine (BA) and 2, 4-Dicholophenoxyacetic acid (2, 4-D) while the organogenic response was found remarkable only in BA supplemented medium. Both types of explant markedly influenced callus formation while organogenesis was noticed only in internode explants. The number of shoots formed in internode explants was greater in the medium supplemented with 0.5ÂµM BA and registered 6.86 numbers of shoot. The regenerated shoots transferred to half MS medium supplemented with 2mg/l IBA produced 75% rooting followed by 66% in IAA supplemented medium. The plantlets raised in vitro were successfully hardened to ex vitro conditions.